The Effect of Sales Promotion, Product Quality, and E-Word Of Mouth on Shopee Live on Impulsive Buying Behavior Among University Students - Naily Fitria Faroha; Rizky Eka Febriansah; Mochamad Rizal Yulianto; Lilik Indayani (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine the influence of sales promotion, product quality, and e-word of mouth on Shopee Live on impulsive buying behavior among Muhammadiyah University Sidoarjo students. The population in this study is all students at the Muhammadiyah University of Sidoarjo who regularly make purchases on Shopee Live. The sample determination method used a purposive sampling method, with a total of 100 respondents. The data analysis technique uses multiple linear regression analysis techniques. The research results show that sales promotion has a positive and significant effect on impulsive buying behavior, product quality has a positive but not significant effect on impulsive buying behavior, while e-word of mouth has a negative and not significant effect on impulsive buying behavior. The research results show that sales promotion, Product quality, and e-word of the mouth simultaneously have a positive and significant influence on impulsive buying behavior.